2021
DOI: 10.1111/aor.14001
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, inflammation, and peritoneal dialysis: A molecular biology approach

Abstract: The key role of oxidative stress (OxSt) and inflammation for the induction of cardiovascular disease, the leading cause of excess morbidity/mortality in chronic kidney disease and dialysis patients, is known and both the activations of NADPH oxidase and RhoA/Rho kinase (ROCK) pathway are pivotal for their effects. While specific hemodialysis procedures, such as hemodiafiltration with on‐line reinfusion of ultrafiltrate and/or the use of vitamin E‐coated dialyzers, are beneficial for OxSt and inflammation, stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The significant interplay between inflammation and oxidative stress in CKD has been stressed [ 35 , 36 , 37 , 38 ]. Our analyses did not show a significant correlation between the inflammation marker C-reactive protein and Nrf2 protein concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The significant interplay between inflammation and oxidative stress in CKD has been stressed [ 35 , 36 , 37 , 38 ]. Our analyses did not show a significant correlation between the inflammation marker C-reactive protein and Nrf2 protein concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that inhibiting hepatic ROCK could improve oxidative stress and the inflammatory response in hypercholesterolemia ( Ma et al, 2011a ; Ma et al, 2011c ). In this study, we used the p-MYPT-1 as a marker for ROCK activity ( Innico et al, 2021 ), and we showed that p-MYPT-1 is highly expressed in the liver of hypercholesterolemic rats, which indicates that hepatic ROCK pathway expression was increased. After PF treatment, we found that p-MYPT-1 expression was significantly reduced, which also showed that PF could reduce hepatic oxidative stress and the inflammatory response, and these results are consistent with our previous research.…”
Section: Discussionmentioning
confidence: 99%
“…In peritoneal dialysis, oxidative stress has been reported only in terms of increased AGEs, and other pro-oxidants derived by glucose [90]. Very recently, by using a molecular biology approach, we have observed in peritoneal dialysis patients that, oxidative stress is increased by peritoneal dialysis procedure as shown by the significantly increased levels of oxidative stress markers such as p22 phox , ROCK activity (MYPT1) and ferritin levels which all further increased after 6 months [91], therefore the use of more biocompatible dialysis solutions containing different glucose polymers such as icodestrin should be considered for their possible beneficial effects on oxidative stress and inflammation ( ).…”
Section: Oxidative Stress and Dialysis Proceduresmentioning
confidence: 96%